Measurement of radionuclides and trace metals concentration in surface sediments from the coastal zone of Lavreotiki peninsula - Michalopoulou-Petropoulou, V.; Tsabaris, C.; Patiris, D. L.; Androulakaki, E. G.; Eleftheriou, G.; Kokkoris, M.; Pappa, F. K.; Vlastou, R. (HNPS Advances in Nuclear Physics, 2019)
This work presents the results of a preliminary study at the coastal zone of the Lavreotiki peninsula, concerning radionuclide and trace metal concentration measurements in sediment samples collected from the seabed of four local gulfs and the corresponding beaches. The radionuclide activity concentrations were determined by means of gamma-ray spectroscopy and the concentration of trace metals by the XRF method. The observed radionuclide levels of both seabed and beach sediment are considered relatively low to medium, in comparison with international values of activity concentration in soil. For most of the trace metals, high concentrations were measured in comparison with guidelines, especially for As, Mn, Pb and Zn.